Learning (by) Feeling: A Cross‐Cultural Comparison of the Socialization and Development of Emotions. (June 2015) - Röttger‐Rössler, Birgitt; Scheidecker, Gabriel; Funk, Leberecht; Holodynski, Manfred
Abstract Although much has been written about "socialization" and "emotion" in different cultures, these two topics have rarely been systematically combined and analyzed from the perspective of ontogenetic development. Drawing on approaches from developmental psychology and cultural anthropology, we examine how cultural models of emotion and their corresponding emotionally arousing child‐rearing practices lead to culture‐specific pathways of emotion development among the Bara (Madagascar) and the Tao (Taiwan). We focus especially on socializing emotions, which we define in terms of their function to orient individuals toward cultural norms and values and to inculcate social conformity. Based on empirical data gathered in long‐term ethnographic field studies, we provide evidence that the Bara emphasize "fear" and the Tao "anxiety" as focal socializing emotions.